Implementasi Nilai-Nilai Pancasila Terhadap Budaya Beretika Untuk Generasi Milenial Sebagai Upaya Meningkatkan Rasa Nasionalisme - Bella Ayu Permata Sari; Galuh Citra Ayu Wangi; Risma Dyah Mawarti; Dinda Ayu Anitasari; Kelola Puji Prihatini (Al Yasini : Jurnal Keislaman, Sosial, hukum dan Pendidikan, 2021)
Abstract This article discusses the concept of an ethical culture centered on human (thoughts and feelings) which is the basis of an action. The purpose of making this article is (1) to identify the extent to which ethical etiquette towards the millennial generation (2) to identify the sense of nationalism of the millennial generation. Collecting data by literature observation, document study or triangulation. The research method used in this study is a literature review, namely the existing literature. Data analysis with qualitative descriptive method. The results obtained in this study are as follows: first, the implementation of Pancasila values. Second, the impact of the ethical culture of the millennial generation. Third, increase the sense of nationalism. Keywords : Pancasila, Ethics, Nationalisme